Falla cardíaca avanzada (2016)
ABSTRACT: Advanced heart failure is a serious disease with persistent symptoms and severe functional limitations, despite optimal medical management. Methodology: We followed the steps defined in the Methodological Guide for the Preparation of Clinical Practice Guidelines and Economic Evaluation in the General System of Social Security of the Colombian Ministry of Health and Social Protection to develop the clinical practice guidelines based on evidence (GPC). Results: In this issue we present the recommendations for advanced heart failure. Conclusion: There are some treatment alternatives for this group of patients, such as ventricular assistance devices and heart transplantation, which had proven to change mortality and improve functional class.